The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1097/01.fbp.0000224386.86615.e0
|View full text |Cite
|
Sign up to set email alerts
|

Localized injections of midazolam into the amygdala and hippocampus induce differential changes in anxiolytic-like motor activity in mice

Abstract: Various strains of mice display a reliable increase in motor activity in response to benzodiazepines given at low to moderate doses. This hyperactivity has been described as both an anxiolytic-associated increase in exploratory activity and a nonspecific stimulant effect controlled by central neural mechanisms separate from those involved in the anxiolytic-like effects. The purpose of the current study was to investigate the neural circuitry underlying the hyperactivity effects of benzodiazepines in mice. Spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 53 publications
(72 reference statements)
1
12
0
Order By: Relevance
“…administration of MG for 6 days reduced anxiety-like behavior in the elevated plus maze. The studies presented here build on those of Hambsch et al (2010) by administering MG to the BLA, which is strongly associated with anxiety-like behavior [8,9,1113]. Taken together with prior studies, our data suggest that Glo1 regulates anxiety-like behavior through neurocircuitry typically associated with anxiety-like behavior.…”
supporting
confidence: 79%
See 3 more Smart Citations
“…administration of MG for 6 days reduced anxiety-like behavior in the elevated plus maze. The studies presented here build on those of Hambsch et al (2010) by administering MG to the BLA, which is strongly associated with anxiety-like behavior [8,9,1113]. Taken together with prior studies, our data suggest that Glo1 regulates anxiety-like behavior through neurocircuitry typically associated with anxiety-like behavior.…”
supporting
confidence: 79%
“…Neuroimaging studies have reported differences in amygdala-prefrontal circuitry in patients with anxiety disorders [10]. Additionally, direct injection of midazolam, a positive allosteric modulator at GABA-A receptors (benzodiazepine), into the BLA reduces anxiety-like behavior in mice [11]. However, because Glo1 expression and MG production occur in all tissues and all brain regions, the role of the BLA in mediating the effects of MG on anxiety-like behavior have not been explored.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The lateral and basolateral nuclei of the amygdala express high levels of α1-GABA A Rs, and are primary sites involved in many behavioral responses induced by BZs (Hevers and Luddens, 1998; Teuber et al, 1999; Pirker et al, 2000; Smith, 2001; Kaufmann et al, 2003; Kopp et al, 2004; Savic et al, 2005; Heldt and Ressler, 2006; Engin and Treit, 2008). To address these issues, the current study examined the behavioral, pharmacological and compensatory consequences of targeted α1-GABA A Rs deletion in the amygdala of adult mice.…”
Section: Introductionmentioning
confidence: 99%